2017
DOI: 10.1080/00223980.2017.1372349
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Adolescents' Depressive Symptoms: The Mediating Role of Future Time Perspective

Abstract: This study investigated the relations between maternal and paternal rearing practices and adolescents' depressive symptoms, and whether time perspective in adolescence explains these links. The sample included 306 students (158 girls), aged between 10.83 and 14.42 years. Adolescents completed questionnaires assessing their perceptions of maternal and paternal acceptance and psychological control, and of their future time perspective and depressive symptoms. Adolescents who rated their mothers as more accepting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Negative thoughts about the future, the self, and the world are the elements of Beck's cognitive theory of depression (Beck, 1979), and these aspects partly overlap with the concept of negative future orientation. Overall, previous literature on the link between future orientation and depression found that a more positive future orientation was linked to fewer depressive symptoms in both adolescent and young adult samples (Allwood, Baetz, DeMarco, & Bell, 2012;Diaconu-Gherasim, Bucci, Giuseppone, & Brumariu, 2017;Hirsch et al, 2007). There is also some evidence supporting the possible protective and moderating role of a positive future orientation in the link between depression and suicide (Chin & Holden, 2013;Hamilton et al, 2015).…”
Section: Future Orientation Depression and Sympathy For Vrmentioning
confidence: 75%
See 1 more Smart Citation
“…Negative thoughts about the future, the self, and the world are the elements of Beck's cognitive theory of depression (Beck, 1979), and these aspects partly overlap with the concept of negative future orientation. Overall, previous literature on the link between future orientation and depression found that a more positive future orientation was linked to fewer depressive symptoms in both adolescent and young adult samples (Allwood, Baetz, DeMarco, & Bell, 2012;Diaconu-Gherasim, Bucci, Giuseppone, & Brumariu, 2017;Hirsch et al, 2007). There is also some evidence supporting the possible protective and moderating role of a positive future orientation in the link between depression and suicide (Chin & Holden, 2013;Hamilton et al, 2015).…”
Section: Future Orientation Depression and Sympathy For Vrmentioning
confidence: 75%
“…Although associated, evidence has however shown that depression and future orientation are two distinct constructs. Depression involves negative and emotional interpretations, as well as a generalized pessimism about the future that are not part of future orientation, which in contrast refers to specific beliefs toward the future (Chin & Holden, 2013; Diaconu-Gherasim et al, 2017). Although the relation between depression and future orientation is still in need of further investigation, these findings suggest the importance of considering one’s future orientation when investigating the impact of depressive symptoms on emotional-behavioral adjustment outcomes (e.g., suicide, delinquency).…”
Section: Future Orientation Depression and Sympathy For Vrmentioning
confidence: 99%
“…Romanian researchers have studied parental practices mainly from the perspective of clinical, developmental, and positive psychology. Those based on clinical conceptual models explored the negative outcomes of low acceptance or/and high parental control as: adolescents' perfectionism (Damian, Stoeber, Negru-Subțiricȃ, & Bȃban, 2013) and depressive symptoms (Diaconu-Gherasim, Bucci, Giuseppone, & Brumariu, 2017). In developmental studies association between parental practices and identity development in adolescence (Negru-Subțiricȃ, Pop, Luyckx, Dezutter, & Steger, 2016 and relationship between mother-child similarities in value orientations in adolescence and perceived maternal parenting (Friedlmeier & Trommsdorff, 2011) were highlighted.…”
Section: Parenting In Romanian Familymentioning
confidence: 99%
“…The mother’s behavior, based on acceptance and warm relations, fulfills the primary need for affection, while the father figure has been linked to greater intellectual functioning, enhanced self-concept and improved academic success (DuBois, Eitel, & Felner, 1994; Wagner & Phillips, 1992). The studies conducted with the Romanian samples of early adolescents suggest that mothers may influence a child’s adjustment (i.e., depressive symptoms) primarily by assuming a nurturing role, whereas the father’s influence may be rooted in the level of parental control and discipline (Diaconu-Gherasim, Bucci, Giuseppone, & Brumariu, 2017). These results were explained by the fact that fathers interact less often with their children, and the interactions are frequently around instrumental goals (e.g., school achievement; Collins & Russell, 1991).…”
Section: Parental Rejection and Achievement Goalsmentioning
confidence: 99%